Monitoring Kwh Meter Digital Berbasis IoT dengan Integrasi Web - Sujono, Sujono; Khafidhoh, Nur; Khalimatus Sa'diyah (AMIK, 2024)
KWH digital meter (KWh digital meter) is a device that has the ability to measure the amount of electric energy. A microcontroller-based digital KWH meter monitoring system with web integration has been designed and developed to improve the efficiency of monitoring electricity consumption. The system uses a PZEM-004T sensor to measure power consumption in real time, with a microcontroller as the primary controller and a web platform as the user interface. The Wemos D1 Mini serves as a control center, processing the data from the sensor and sending it to the web server for display. Testing and calibration of the tool showed that the average current error percentage of 0.65%, showed an excellent degree of accuracy in measuring the current. The average voltage error percentual of 2.18% showed fairly good accurate measurement of the voltage, although there are few deviations that are still bounded in acceptable tolerances. The mean power error percent of 2.51% showed sufficiently good accurately measuring electricity consumed, with the deviation remaining within acceptable limits for power consumption monitoring applications. By considering the average error percent result for current, voltage and power, it can be concluded that the microcontroller-based digital KWH meter that has been made has a good degree of precision and can be used in the monitoring of electricity use.